Perancangan Sistem Informasi Pemasaran Online Pengrajin di Bekasi (Studi Kasus: BM) - Fitriana, Rina; Kurniawan, Wawan; Sarah, Syamila (Metris: Jurnal Sains dan Teknologi, 2016)
Marketing is a very important thing in doing business.Problem facedby craftsmen are limitedmarketing channels through social media by manually disseminate product information.Research purposes are develop the marketing of small and medium enterprises by using a web based information system.Methodology used is marketing analysis with Segmentation, Targeting and Positioning (STP) and Product, Price, Place, and Promotion (4P analysis), and SWOT (Strength, Weakness, Opportunity, Thread) analysisand methods of object oriented analysis and design withusing Unified Modeling Language (UML). Analysis undertaken to review the current system and identify the need of system. Marketing strategy that will be developed is to incease the variety of products, following the exhibition, and make the marketing information system online. Evaluation is measured through the increase in the skill of partner in operating marketing information system and the result the small medium enterprises can operate this system. The results of this research are marketing analysis and marketing information system online.